(untitled) (Journal of Hama University, 2019)
Evaluation is the educational process in the kindergarten stage, and measures the educational return of the child through the practice of various activities adopted curriculum and the achievement of specific educational goals. The study was aimed to develop children’s vocabulary in kindergartens through a program of narrative activities and assessment cards used to increase the child’s linguistic wealth by allowing them to engage in dialogue and conversation and to create a readiness to read and write through stimulating activities. The study uses a series of narrative activities suitable for children’s experiences in the Ministry of Education for children of the third category of age (5-6) years, and calendar cards designed by the researcher , and then uses analysis methods such as percentages and T test.The study concludes the following observations: The researcher finds a clear improvement in dialogue, conversation and verbal expression among the sample members. There is a need to train teachers to use planning and evaluation to re-plan as needed.